Performance of newly introduced broadbean genotypes under rainfed conditions of Duhok Province - Sulaiman, Dalilla Nadhir; Ibrahim, Darsim Mame; Omer, Fathi Abdulkareem (Sulaimani Journal for Pure and Applied Sciences, 2018)
This experiment was conducted at Malta Agriculture Research Center, Duhok Province during growing seasons 2014/15, 2015/16, and 2016/17 to investigate the performance of twelve newly introduced genotypes of fababean under rainfed conditions of Duhok province. The lack of improved varieties and well adapted by the farmers in the study area is the main challenge for the Agricultural Research Centers in Iraqi Kurdistan Region; accordingly twelve newly introduced genotypes of fababean namely: FLIP12-153Fb, FLIP12-154fB, FLIP12-137FB, FLIP12-155FB, FLIP12-142FB, FLIP12-143FB, FLIP12-144FB, FLIP12-145FB, FLIP12-147FB, FLIP12-149FB, Aquadulce and Elisar, along with a local check variety were evaluated for their yield and yield components under rainfed conditions of Duhok province. The results indicated that there were slight variations among genotypes in all growing seasons for growth measurements. On the other hand, there were significant differences among the studied genotypes in respect to yield and its component parameters. In combine analysis where the seasons considered as replications, the higher grain yield was harvested from FLIP12-147FB variety followed by FLIP12-153Fb, FLIP12-143FB, FLIP12-155FB. Therefore, these genotypes can be recommended to the farmers located at the targeted area.
Keywords: Broadbean; Genotypes; Rainfed; Seed yield